Structure, optical and electrical properties of (Cu1-xAgx)2ZnSn(S, Se)4 alloy thin films for photovoltaic application. (July 2018) - Jiang, Yuhong; Yao, Bin; Li, Yongfeng; Ding, Zhanhui; Luan, Hongmei; Jia, Jinhuan; Li, Yan; Shi, Kun; Sui, Yingrui; Zhang, Bingye
Abstract: We fabricated the (Cu1-x Agx )2 ZnSn(S, Se)4 (CAZTSSe) (0 ≤ x ≤ 0.25) alloy thin films by a simple solution approach combined with a post-selenization technique, and investigated the influence of Ag contents on structure, morphology, band gap as well as electrical property of CZTSSe thin films. The results showed that Cu + cation in Cu2 ZnSn(S, Se)4 (CZTSSe) films was replaced by Ag + cation, forming homogeneous CAZTSSe (0 ≤ x ≤ 0.25) alloy thin films. The crystal structure and the band gap of CAZTSSe (0 ≤ x ≤ 0.25) alloy thin films are influenced by Ag/(Cu+Ag) ratios. The incorporation of Ag is found to accelerate the grain growth and increase the grain size. The optical band gap of CAZTSSe alloy thin films can be continuously tuned in the range of as Ag content from x = 0 to x = 0.15. Furthermore, Hall measurement results indicate that all CAZTSSe alloy thin films showed p-type conductivity and hole concentration decreased with the increasing the Ag contents.